PENGEMBANGAN BAHAN AJAR (LKPD) MATEMATIKA BERBASIS GAME UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA KELAS 2 SDN 15 NTOBO KOTA BIMA - Rahmawati; Lastuti, Sri; Khatimah, Husnul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to explain the improvement of students' numeracy literacy skills through the implementation of game-based mathematics teaching materials (LKPD) at SDN 15 Ntobo, Kota Bima. This research was conducted using the Research and Development (R&D) method with the ADDIE model. Research data was collected using expert validation questionnaires for media and content, teacher and student response questionnaires, as well as students' learning outcomes after using the LKPD. The assessment by media experts resulted in an average score of 94.6% (categorized as highly feasible), while content experts gave an average score of 93.6% (also categorized as highly feasible). Furthermore, the evaluation by three teacher respondents showed an average score of 99% (highly practical) for the first respondent, 98.1% (highly practical) for the second respondent, and 99% (highly practical) for the third respondent. Meanwhile, student responses obtained an average score of 93.6%, indicating that the LKPD was considered highly practical for implementation. The use of the developed LKPD product in the learning process demonstrated a significant increase in the average learning outcomes from 69.75% to 89.875%. The N-Gain test showed an average score of 0.66, categorized as moderate.